2012
DOI: 10.1007/s00701-012-1327-z
|View full text |Cite
|
Sign up to set email alerts
|

Patients with idiopathic trigeminal neuralgia have a sharper-than-normal trigeminal-pontine angle and trigeminal nerve atrophy

Abstract: A sharp trigeminal-pontine angle on the affected side was found in idiopathic TN patients by FIESTA imaging. This suggests that a sharp trigeminal-pontine angle increases the chance of neurovascular compression on the medial side of the trigeminal nerve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 26 publications
0
18
0
1
Order By: Relevance
“…Numerous studies have assessed the pattern of neurovascular conflict (NVC) due to crowding of the cisternal space and the neurovascular structures that occupy that space and its association with symptoms of TN. 5,7,17,18 Park and colleagues retrospectively reviewed MRI studies of 26 patients with unilateral TN treated with Gamma Knife radiosurgery. 17 They found a significantly smaller crosssectional area in the cerebellar-pontine angle cistern in the symptomatic side compared with the asymptomatic side, as well as a shorter cisternal segment of the trigeminal nerve on the affected side.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have assessed the pattern of neurovascular conflict (NVC) due to crowding of the cisternal space and the neurovascular structures that occupy that space and its association with symptoms of TN. 5,7,17,18 Park and colleagues retrospectively reviewed MRI studies of 26 patients with unilateral TN treated with Gamma Knife radiosurgery. 17 They found a significantly smaller crosssectional area in the cerebellar-pontine angle cistern in the symptomatic side compared with the asymptomatic side, as well as a shorter cisternal segment of the trigeminal nerve on the affected side.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,7,9,10,17 In a retrospective study of 30 patients with idiopathic TN, Ha and colleagues demonstrated that, on preoperative FIESTA MRI, there was significantly more atrophy at the cisternal segment of the trigeminal nerve on the affected side than on the unaffected side compared with the affected and unaffected sides of age-and sexmatched control patients with hemifacial spasm. 5 Of note, these authors also found a significant association between the sharpness of the trigeminal-pontine angle on the affected side compared with the unaffected side, which was not found in the control group. Likewise, a study by Erbay and colleagues looked at using MRI studies obtained in 36 patients with unilateral TN treated with Gamma Knife radiosurgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that a sharp trigeminal pontine angle may be a useful additional diagnostic factor for idiopathic TN, facilitating the NVC (21,22).…”
Section: A B a Bmentioning
confidence: 99%
“…Large arteries are more likely to cause higher RD and more easily to make trigeminal nerve demyelination, while small arteries are not. Some studies [ 4 , 5 , 10 , 12 ] showed that trigeminal nerve demyelination is prevalent in TN patients. Demyelination causes destruction of the trigeminal nerve integrity, which leads to TN.…”
Section: Discussionmentioning
confidence: 99%